La inteligencia musical en la enseñanza de la matemática en los niños de educación inicial ll de la unidad educativa José María Román de la ciudad de Riobamba - Herrera Llambo, Victoria Isabel (2024)
The main objective of this study was to determine how musical intelligence influences the mathematical teaching of children in early education II, supported by qualitative, descriptive research with a non-experimental design, using observation as a technique and supported by the observation sheet. The study was carried out in the “José María Román” Educational Unit, in the city of Riobamba, the total population was 20 Initial II students and due to the magnitude of its size, the same population was considered as a sample. The findings point to the fact that the entire population considers music as part of mathematics class, which is why they use a sound instrument for this purpose, delving into skills in the subject. 90% executed movements with their body, following musical patterns and maintained concentration after a song. Everyone memorizes basic concepts in the activity and is interested in learning mathematics. Music provides reinforcement in the teacher's explanation, presenting a significant advance in relation to strengthening learning with respect to mathematics. Proving that this tool is powerful for the dynamic teaching-learning of the subject.